Evaluation of the Implementation of Child-Friendly ‎Madrasah Management in Madrasah Ibtidaiyah, ‎Bandar Lampung City - Doni Sastrawan; Yuli Yanti (GHAITSA : Islamic Education Journal, 2026)
This study aimed to evaluate the implementation of child-friendly madrasah management in a selected Madrasah Ibtidaiyah in Bandar Lampung, Indonesia, using the Context, Input, Process, and Product (CIPP) evaluation framework. A qualitative evaluative approach with a single-case study design was employed. Data were collected through semi-structured interviews with the madrasah principal, teachers, students, parents or guardians, school committee members, and relevant educational personnel, complemented by non-participant observations. The data were analysed through theoretically informed thematic analysis by combining deductive coding based on the CIPP dimensions with inductive identification of emerging themes, while the trustworthiness of the findings was strengthened through source and method triangulation. The findings showed that the programme was contextually relevant to students’ needs and supported by anti-violence, anti-bullying, and positive-discipline policies. The input component was characterised by the existence of an implementation team, teacher guidance, basic facilities, complaint channels, and parental involvement, although staff understanding, facilities, and programme resources remained uneven. At the process level, child-friendly principles were reflected in respectful teacher–student interaction, nonviolent discipline, student participation in classroom learning, complaint handling, and communication with parents; however, systematic monitoring, documented follow-up, and student involvement in institutional decision-making were not yet fully developed. The product component indicated positive perceived outcomes in student safety, classroom comfort, discipline, confidence, and willingness to attend school. Overall, the programme was relationally established but managerially incomplete. Its sustainability requires stronger institutional quality assurance through continuous staff development, measurable evaluation indicators, transparent complaint mechanisms, improved facilities, and meaningful student participation.